PARALU TU MURI MADA (PERLU UNTUK HIDUP): METAFORA KONSEPTUAL NYANYIAN DI ATAS POHON LONTAR (Paralu Tu Muri Mada (Need it for Life): The Conceptual Metaphor of Songs on the Lontar Tree) - Sine, Junaity Soften; Mata, Rosdiana (Kantor Bahasa Provinsi Sulawesi Tenggara, 2023)
The oral singing tradition on the Lontar Tree while tapping the flowers of the Lontar Tree in Sabu Island is interesting to be investigated from its metaphorical language use – employing the Conceptual Metaphor Theory by Lakoff and Johnson. Therefore this study investigated (1) the conceptual metaphor mapping; (2) the cultural-historical and social situation that triggers the metaphorical language; and (3) the local wisdom values reflected in the songs. A qualitative approach with ethnography design was applied to the interview, observation, and documentation of six farmers on the Island of Sabu. It found (1) eight conceptual metaphor mappings, namely people are plants, plants are people, people are animals, social relations are containers, happiness is cold river, people are machine, manner is taste, and marriage is a sea journey; (2) contextual factors: history and belief of the local people, flora and fauna from daily life, a sea community of people, and people who travel; (3) local wisdom values: normative values: advice for love and family relation, respect and care for the Lontar Tree, and historical values. Tradisi menyanyi di atas Pohon Lontar ketika menyadap nira di Pulau Sabu menarik untuk diteliti dari sisi penggunaan kata-kata dalam syair lagu secara metaforis – dengan Conceptual Metaphor Theory Lakoff dan Johnson. Penelitian ini menelisik (1) pemetaan metafora konseptual; (2) latar kultural-historis dan sosial penggunaan metafora konseptual; dan (3) nilai-nilai kearifan lokal yang muncul dalam syair lagu. Desain Etnografi dalam Pendekatan Kualitatif dilakukan dengan wawancara, observasi dan dokumentasi terhadap enam subjek penyadap nira di Pulau Sabu. Ditemukan (1) pemetaan 8 metafora konseptual yakni manusia adalah tanaman, tanaman adalah manusia, manusia adalah binatang, relasi sosial adalah wadah, kebahagiaan adalah sungai yang dingin, manusia adalah mesin, perilaku adalah cita rasa, dan pernikahan adalah perjalanan laut; (2) Latar penggunaan metafora konseptual: sejarah dan kepercayaan masyarakat, flora dan fauna dalam kehidupan keseharian, kehidupan yang dekat dengan laut, dan masyarakat yang merantau; (3)nilai-nilai kearifan lokal: nilai normative nasihat seputar percintaan dan keluarga, menghargai dan merawat Pohon Lontar, dan nilai historis.